Covering Migration—in Africa and Europe: Results from a Comparative Analysis of 11 Countries. (2nd January 2022) - Fengler, Susanne; Bastian, Mariella; Brinkmann, Janis; Zappe, Anna Carina; Tatah, Veye; Andindilile, Michael; Assefa, Emrakeb; Chibita, Monica; Mbaine, Adolf; Obonyo, Levi; Quashigah, Timothy; Skleparis, Dimitris; et al.
ABSTRACT: While the issue of migration has heavily impacted on public debates in the Global North, much less is known about coverage of migration in the Global South. This pilot study sets out to de-westernize the discussion, by analyzing and comparing news coverage in migrants' destination countries and countries of origin. The study's focus is on media coverage of migration from Africa towards Europe. The paper builds upon prior studies on the coverage of migrants and refugees. A consortium of African and European researchers has conducted a comparative content analysis of migration coverage in 22 opinion-leading newspapers in six European and five sub-Sahara African countries. The study has retrieved 1, 512 articles which have appeared in 2015/16. The topic was much less salient in African countries, with only 175 articles found in the African news outlets under study. Coveragein the European destination countries was dominated by domestic issues like border security and migration policy, but also paid attention to the actual migrants—who received much less coverage in the sending countries. Coverage of migration in African media was more negative and focused on disasters at sea. Both African and European media ignored the causes of migration.